DIMENSIONS OF HOSPITAL ETHICS LEGAL STUDIES IN T HE ERA OF DIGITALIZATION - SEPRIANDISON SARAGIH (INTERNATIONAL JOURNAL OF MULTI SCIENCE, 2024)
The aim of this research is to determine the impact and era of the industrial revolution 4.0 in the health sector, as well as the challenges faced by health ethics laws in the era of the industrial revolution 4.0. The method used is a qualitative descriptive method using a phenomenological approach. We examine the data using critical data coding, in-depth interpretation and drawing conclusions which are the answers to this research question by adhering to the principles of high validity and reliability. Next, we describe the data in the findings section by adding criticism and discussion to understand whether the data is relevant to answering the problem. For the reporting stage, we chose qualitative data reporting based on data or literature reviews, which we limited to information and data released between 2010 and 2021 to look for the latest information and data. The results of the discussion carried out are that health ethics is taken from the word ethics, which is a discipline that begins with identifying, organizing, analyzing and deciding human behavior by applying principles to determine good behavior in a situation at hand. Industrial Revolution 4.0 is a phenomenon that combines cyber technology and automation technology. Industrial Revolution 4.0 is also known as "cyber physical system". The health sector is the sector most likely to benefit from the Industrial Revolution 4.0 because of the joining of physical, digital and biological systems. The conclusion from this research is that there are changes and advances in the health sector, especially in dental implants, cosmetic surgery and oncology. The era of industrial revolution 4.0 presents challenges that are not easy in the health sector. Apart from the abundant demographic bonus, other challenges also exist in the realm of health service technology innovation.